(untitled) (Dhaka University Journal of Science, 2020)
We report the surface morphology, structural propertiesand surface characterization of copper(II) oxide by scanning electron microscope, energy dispersive X-ray spectroscopy, Fourier transformation infrared spectroscopy, attenuated total reflection infrared spectroscopy and X-ray diffraction. All the data of analysis were consistent with each other and bear the evidence for the purity of the prepared oxide. Kubelka-Munk (K-M) theory is used for the determination of direct band gap of the prepared oxide from UV-visible reflectance spectrum. The band gap value of the bulk material was found to be 4.15 0.05 eV from F(R) versus energy and (F(R) hv)n versus energy plots, with n=1/2 and n=2 Molar magnetic susceptibility and effective magnetic moment of the oxide are 3.393×10-4(cgs) and 0.895 BM respectively which suggest that the oxide is paramagnetic. Catalytic activity was investigated by the study of adsorption of brilliant red (BR) on the surface of prepared oxide in aqueous medium at room temperature. Adsorption isotherm shows that BR moleculesare adsorbed layer by layer on the surface of oxide. Study of the adsorption phenomenon in this work suggest that copper(II) oxide has significant adsorptive and catalytic property. Dhaka Univ. J. Sci. 68(1): 7-12, 2020 (January)